KUFRI MANIK: A RED SKINNED BIOFORTIFIED POTATO VARIETY - Ms, Dalamu (Potato Journal, 2023)
ABSTRACT: Kufri Manik is a medium maturing, main season, nutrient-rich table potato variety suitable for cultivation in Eastern plains. It is a clonal selection from the cross between Kufri Arun √ CP3192. Its plants are tall with field resistance to late blight. The variety produces attractive, deep red, round shaped tubers with medium eyes and yellow flesh. Kufri Manik is nutrient-dense variety by virtue of high anthocyanin (68 mg/100g FW), phenols (71 mg/100g FW), Zinc (33 ppm), Iron (30 ppm) as compared to red skin control varieties like Kufri Lalima and Kufri Lalit. It is fertilizer responsive and can yield 23-25 t/ha under optimum agronomical practices. Kufri Manik has performed well in multi-location trials conducted under AICRP on Potato and has been recommended for cultivation in eastern plains (Bihar, Orissa, West Bengal, Assam and Eastern Uttar Pradesh).